Improving hypertension knowledge, medication adherence, and blood pressure control: A feasibility study. Issue 19 (19th April 2021) - Marseille, Beatrice Remy; Commodore‐Mensah, Yvonne; Davidson, Patricia M.; Baker, Deborah; D'Aoust, Rita; Baptiste, Diana‐Lyn
Abstract: Aims and Objectives: To examine the feasibility of a culturally tailored education programme for Haitian immigrants diagnosed with hypertension. Background: Hypertension is a major public health problem, impacting more than 26% of the global population. The overall prevalence of hypertension is 45.4% in the United States with nearly 80, 000 deaths due to hypertension in 2015. African Americans and other Black populations living in the U.S. are disproportionally affected by hypertension. Design: Pre‐test and post‐test feasibility study. Methods: A convenience sample of forty‐four participants who identified as Haitian immigrants was enrolled in this evidence‐based education programme. The intervention included culturally tailored education focused on improving knowledge, medication adherence and blood pressure. Outcomes were measured using the Hill‐Bone Medication Adherence Scale and Hypertension Knowledge Test. The SQUIRE 2.0 guidelines were used for reporting outcomes. Results: Of the participants that completed the study (N=42), the mean age was 61.95 (± 9.75) years and 59% were female. Baseline systolic and diastolic blood pressures were 143 (±18.15) and 85 (±7.23), respectively. Six weeks after the intervention, there was a significant decrease in mean systolic, 126 (±12.07) and diastolic 78.50 (± 7.23) blood pressures. An increase in medication adherence and hypertension knowledge was also noted at the six‐week follow‐up period. Conclusion: The feasibility of healthcare provider implementation of a culturally tailored intervention to manage hypertension has been demonstrated. However, future research is warranted to gain a more in‐depth understanding of how to approach hypertension management among Haitians and other Black immigrant communities. Relevance to clinical practice: Advanced practice nurses are uniquely qualified to implement evidence‐based programmes that improve patient knowledge and adherence to hypertension management. Through tailoring and adopting an evidence‐based methods for educating patients about medication adherence and adequate blood pressure management, there is a potential to see improvements in patient outcomes.